Consolidation of the perinatal care system and workload of obstetricians: an ecological study in Japan - Hattori, Sanae; Sakata, Nobuo; Ishimaru, Miho; Tamiya, Nanako (Frontiers in Global Women's Health, 2023)
Objectives We examined the relationship between consolidation of delivery and the workload of obstetricians working at perinatal centers. Methods We conducted a descriptive analysis using perinatal care areas classified into three types (metropolitan, provincial, and rural). We calculated the Herfindahl–Hirschman Index (HHI) as an index of consolidation and the proportion of the deliveries at clinics as an indicator of the low-risk deliveries and the deliveries per center obstetrician as an indicator of obstetricians’ workload. We used >150 deliveries yearly as an excess indicator. The correlation between the HHI and obstetricians' workload and the proportion of deliveries at clinics was examined using the Pearson correlation coefficient. Results The proportion of areas with >150 deliveries yearly was higher in the consolidated areas. In provincial areas, obstetricians’ workload was positively correlated with the HHI and was negatively correlated with the proportion of deliveries at clinics. Conclusions The obstetricians' workload may be increasing where more consolidation occurs. In provincial areas, the center obstetrician's workload could be reduced not only by consolidation but also by sharing the role of handling low-risk deliveries with clinics and hospitals with obstetric units other than perinatal centers.